Synthesis and Evaluation of Antimicrobial Activity of 1-Phenylpyrazolo[4,5-c]quinolin-4-one - Subashini, R.; Kawya, A.P.; Arulprakash, G. (Asian Journal of Chemistry, 2010)
A series of 1-phenylpyrazolo[4,5-c]quinolin-4-ones, carrying appropriate substituents at the quinoline ring have been synthesized in good yields involving the condensation of 4-chloro-3-formylquinolin-2[1H]ones with phenylhydrazine using triethylamine as a base. All the synthesized compounds were evaluated for their antibacterial activities.